Cultured Meat and Australia's Generation Z - Bogueva, Diana; Marinova, Dora (Frontiers in Nutrition, 2020)
This exploratory study of Gen Z consumers (n=227) examines perceptions and opinions about cultured meat of young adults residing in Sydney, Australia. It uses an online survey and describes the findings quantitatively and through the words of the study participants. The results show that the majority (72%) of the participants are not ready to accept cultured meat; nonetheless, many think that it is a viable idea because of the need to transition to more sustainable food options and improve animal welfare. When faced with a choice between different alternatives to farmed meat, a third of the participants reject cultured meat and edible insects but accept plant-based substitutes finding them more natural. Concerns about masculinity and betraying Australia as a country of quality animal meat are also raised. A significant number of young people (28%) however are prepared to try cultured meat. Environmental and health concerns may influence a broader section of society to embrace this novelty. With its power as the emerging new consumers, Gen Z is putting the future of cultured meat under scrutiny.